AlGaN/GaN MIS‐gate HEMTs with SiCN gate stacks. Issue 5 (6th February 2013) - Kobayashi, K.; Kano, M.; Yoshida, T.; Katayama, R.; Matsuoka, T.; Otsuji, T.; Suemitsu, T.; Krishna, Sanjay; Plis, Elena
Abstract This paper reports AlGaN/GaN metal‐insulator‐semiconductor (MIS)‐gate high electron mobility transistors (HEMTs) with a SiCN gate stack deposited by plasma‐enhanced chemical vapour deposition (PECVD) using hexamethyldisilazane (HMDS) vapor. A transconductance of 69 mS/mm and a current gain cutoff frequency (fT) of 25 GHz are obtained for the SiCN MIS‐HEMTs with a gate length of 0.3 µm. These performances are better than those of the Schottky‐gate reference devices. To clarify the origin of these improvements, we verified the cleaning effect of hydrogen used as a carrier gas for HMDS during the PECVD of SiCN. The results indicate that the hydrogen annealing improves the drain current density and fT as well as it suppresses the current collapse. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)